2022
DOI: 10.1192/j.eurpsy.2022.2339
|View full text |Cite
|
Sign up to set email alerts
|

The role of pre-pandemic depression for changes in depression, anxiety, and loneliness during the COVID-19 pandemic: Results from a longitudinal probability sample of adults from Germany

Abstract: This peer-reviewed article has been accepted for publication but not yet copyedited or typeset, and so may be subject to change during the production process. The article is considered published and may be cited using its DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
3
9
1
2
Order By: Relevance
“…A Norwegian cohort study similarly showed pre-pandemic prevalence of mental disorders of 15.4% and ranging from 9.0% to 14.3% during the early phases of the pandemic (March to September 2020) (Knudsen et al, 2022 ). Our study findings are also similar to a longitudinal German cohort study which highlights that among those who screened positive for depression in 2019, 33.6% and 21.9% also screened positive for depression and anxiety in 2021, whereas among those who did not screen positive for depression in 2019, 9.8% and 6.5% screened positive for depression and anxiety in 2021 (Benke et al, 2022 ). Longitudinal studies with increased number of follow-ups including measures before and during the pandemic are needed to better describe the temporal patterns of anxiety and depression.…”
Section: Discussionsupporting
confidence: 90%
“…A Norwegian cohort study similarly showed pre-pandemic prevalence of mental disorders of 15.4% and ranging from 9.0% to 14.3% during the early phases of the pandemic (March to September 2020) (Knudsen et al, 2022 ). Our study findings are also similar to a longitudinal German cohort study which highlights that among those who screened positive for depression in 2019, 33.6% and 21.9% also screened positive for depression and anxiety in 2021, whereas among those who did not screen positive for depression in 2019, 9.8% and 6.5% screened positive for depression and anxiety in 2021 (Benke et al, 2022 ). Longitudinal studies with increased number of follow-ups including measures before and during the pandemic are needed to better describe the temporal patterns of anxiety and depression.…”
Section: Discussionsupporting
confidence: 90%
“…Considering the increase in the number of infected people during successive waves of the pandemic, decreases in both elevated psychological distress and fear of COVID-19 during the successive waves were notable. In accord with the current findings, a few previous studies have reported decreases in depressive symptoms and anxiety between the pandemic waves during shorter periods (i.e., 8 to 11 months) [ 33 , 34 ]. These decreases in anxiety or fear regarding COVID-19 are understandable considering increased knowledge about COVID-19 and increased available medical resources against the virus, including vaccines and medications.…”
Section: Discussionsupporting
confidence: 92%
“…O tratamento dos transtornos mentais comuns, na atenção básica em saúde, deve, necessariamente, envolver um cuidado multidisciplinar, com mobilização de diferentes profissionais da área da saúde, com o objetivo de oferecer o melhor tratamento possível, em quaisquer condições (ASHCROFT et al, 2021). No cenário da pandemia, isso se mostrou de forma ainda mais aguda, haja vista o aumento do número de casos de ansiedade e depressão durante seu desenvolvimento (BENKE et al, 2022), bem como a resposta dada pelas diferentes áreas de atuação -consubstanciada pelas resoluções de conselhos de classe, a qual faz parte do que legalmente denomina-se de "atenção integral" (BRASIL, 2007). Com a redução dos atendimentos em psicoterapia, há tendência de aumento de sintomas próprios dos TMCs, recidivas e custos gerais para o sistema de saúde, com impacto direto e indireto sobre a atenção básica ou primária em saúde (FREEMAN, 2022;(KRIJNEN-DE-BRUIN et al, 2022).…”
Section: Considerações Finaisunclassified